Moral Training of the Future Lawyers: Historiographic Analysis of the Problem - Denyschyk, Olexiy (Pedagogical Discourse, 2013)
Insufficiently known problem of moral training of students and, in particular, future lawyers, under the conditions of higher educational establishment has been analyzed in the article. Study of the complex of works of outstanding philosophers, pedagogues and lawyers, historic-pedagogical and juridical literature, publications and scientific researches, works of famous writers and poets, allowed us to ground the problem of formation of moral culture and professionally necessary qualities of legal scholars.